CHE495: Hydrocarbon Chemistry / College of Engineering - UiTM, College of Engineering (2018)
This course provides a chemical background of sufficient depth to facilitate an understanding of the organic chemical processes, which occur in industry. Topics covered include organic nomenclature, reaction types and mechanisms, biomolecules and polymers.